Deterioration of coastal groundwater quality in Rameswaram Island of Ramanathapuram District, Southern India - Venkataramann Sivsankar; Thiagarajan Ramachandramoorthy; M. Senthil Kumar (Химия и технология воды, 2013)
A study was carried out in the South-West, North-East and North-West segments dividing the local area of Rameswaram Island to characterize the physico-chemical characteristics of 87 groundwater samples which include pH, electrical conductivity (EC), total dissolved solids (TDS), salinity, total alkalinity (TA), calcium hardness (CH), magnesium hardness, total hardness (TH), chloride and fluoride. heavy inorganic load in majority of the groundwater samples has been estimated due to the salinity, TDS, TH and chloride beyond the threshold level which substantiates the percolation of sea water into the freshwater confined zones. The Water Quality Index and Langeleir Saturation Index have also been calculated to know the potable and corrosive/incrusting nature of the water samples. The results are interpreted based on statistical tools. Greater than 80 % of the samples were found to have exceeded the limit of WHO drinking standard especially in TDS, CH, TA and chloride.